2022
DOI: 10.1038/s41598-022-15088-8
|View full text |Cite|
|
Sign up to set email alerts
|

Sexual practices and HPV infection in unvaccinated young adults

Abstract: The present study aimed to evaluate the association of genital and oral HPV infection among different sexual practices in both sexes. In total, 6388 unvaccinated men and women aged 16–25 years from all state capitals of Brazil were enrolled in through primary care services between September 2016 and November 2017. Genital and oral HPV genotyping was performed using the Roche Linear Array. Poisson regression analysis with robust variance was conducted to examine factors associated with overall HPV infection. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 40 publications
1
6
0
1
Order By: Relevance
“…We found that measures of sexual activity, such as increasing numbers of sex partners, were strongly associated with oral HPV infection; the strongest associations were seen with frequency of oral sex partners (both giving and receiving). This finding has been observed in other regions of the world 7‐9,14,20‐22 . Furthermore, we found that a previous diagnosis of a STI was associated with oral HPV infection, and in particular a previous diagnosis with herpes simplex.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…We found that measures of sexual activity, such as increasing numbers of sex partners, were strongly associated with oral HPV infection; the strongest associations were seen with frequency of oral sex partners (both giving and receiving). This finding has been observed in other regions of the world 7‐9,14,20‐22 . Furthermore, we found that a previous diagnosis of a STI was associated with oral HPV infection, and in particular a previous diagnosis with herpes simplex.…”
Section: Discussionsupporting
confidence: 88%
“…This finding has been observed in other regions of the world. [7][8][9]14,[20][21][22] Furthermore, we found that a previous diagnosis of a STI was associated with oral HPV infection, and in particular a previous diagnosis with herpes simplex.…”
Section: Notementioning
confidence: 59%
See 2 more Smart Citations
“…Apesar do risco menor de transmissão quando comparado com o sexo penetrativo vaginal e anal, o sexo oral também é um meio importante de contágio de IST's. Há quatro formas de transmissão de doenças por meio do sexo oral ou contato oral: transmissão por contato direto com epitélio ou mucosa, cujos mais frequentes são os vírus, como HPV e herpes, destaca-se um aumento do risco de ocorrência de câncer de boca e orofaringe nas infecções por HPV oncogênicos (ANTONSSON et al, 2022;PAULI et al, 2022); através do sangue, em que na presença deste durante o sexo oral, podem ser transmitidos o HIV, a hepatite B, a hepatite C e a sífilis; através das secreções, pode ser transmitida a gonorreia e a Chlamydia; e ainda pela transmissão vertical: o vírus do HPV adquirido no canal de parto da mãe pode se estabelecer na cavidade oral do(a) filho(a), podendo, assim, ser transmitido, posteriormente, à parceria.…”
Section: Introductionunclassified